International Legal Regime Concerning Piracy in the Gulf of Guinea - SERGEEVNA, Anyanova Yekaterina (Journal of Advanced Research in Law and Economics, 2017)
This paper focuses on the problem of piracy consideration in international law. The urgency of this problem can be attributed to the considerable damages it inflicts on the global economy. Despite the general decline in pirate attacks worldwide due to the effective curbing of the notorious Somalian piracy, the situation in the Gulf of Guinea remains critical. Irrespective of the fact that the successful solution of the long-standing Somali pirate crisis came from concerted efforts by various countries (in 2015 – 2016 no attacks in the region were reported), piracy situation in the Gulf of Guinea is not currently considered to be serious enough for international interference. Increased pirate activities in this area are allegedly associated with crude oil shipping through these waters, and also related to political and economic crises in coastal states. It has been repeatedly stressed that the Gulf of Guinea problem requires a comprehensive, all-inclusive approach to the issue of maritime security, and first and foremost this holds for the regional level where countries sharing the coastal line have to gear up their efforts to this effect.